Peningkatan Daya Dukung Pondasi pada Tanah Lempung dengan Perkuatan Kolom Tanah - Ratna Dewi; Hanafiah; Ridho Ustadi (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2020)
One of the problematic soils for construction if the soil is used as a foundation for a construction is clay soil which has relatively low shear strength and bearing capacity. Therefore, it needs an improvement effort to increase the strength of the clay soil. The reinforcement soil column is an alternative effort to improve the soil. This paper presents the results of laboratory-scale experimental on the reinforcement modelling of clay soil columns mixed with 6% rice husk ash (RHA). Modelling was carried out with 6 variations of column groups with constant column length of 67cm. The first three variations are the variation in the distance between columns (s/d) with a fixed diameter of 8 cm. The other three variations are column diameter variations with a fixed s/d ratio. The results showed that the larger the distance between the columns, the smaller the bearing capacity of the soil foundation. If the s/d ratio is constant, it is found that the larger the column diameter, the greater the bearing capacity of the soil foundation. The maximum ultimate bearing capacity of the soil is achieved in variations with a column diameter of 12cm and a distance between columns of 30cm (s/d = 2.5) with a value of 39.56 kPa. This bearing capacity provides a BCR value of 3.75% or almost 4 times the bearing capacity of the unreinforced foundation.